2012
DOI: 10.1080/14783363.2011.637789
|View full text |Cite
|
Sign up to set email alerts
|

Teaching quality in higher education: An introductory review on a process-oriented teaching-quality model

Abstract: For improving the quality of teaching in higher education, besides the organisational focus or the result-oriented and momentary evaluations, attention can be paid to teachers and their 'teaching processes'. With this in mind, the information systems quality (ISQ) laboratory developed a process-oriented model that offered teachers a systematic and incremental way for superior teaching excellence. The model, which is termed teaching capability maturity model (T-CMM), is an application of total quality managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 30 publications
0
34
0
1
Order By: Relevance
“…De Lourdes Machado-Taylor et al (2016) and Rikkerink et al (2016) indicated that academics are a key resource in higher education, and a well-developed motivational mechanism can usually attract academics to contribute to an excellent teaching or research environment; thus, a motivational mechanism certainly has a positive effect on the continuous improvement of higher education quality. In addition, according to Asif et al (2013), Aminbeidokhti et al (2016), and Chen et al (2014), a suitable motivational mechanism will improve the education process quality. Therefore, motivational mechanisms have a positive effect on the continuous improvement of higher education quality.…”
Section: Methods Research Hypothesesmentioning
confidence: 99%
“…De Lourdes Machado-Taylor et al (2016) and Rikkerink et al (2016) indicated that academics are a key resource in higher education, and a well-developed motivational mechanism can usually attract academics to contribute to an excellent teaching or research environment; thus, a motivational mechanism certainly has a positive effect on the continuous improvement of higher education quality. In addition, according to Asif et al (2013), Aminbeidokhti et al (2016), and Chen et al (2014), a suitable motivational mechanism will improve the education process quality. Therefore, motivational mechanisms have a positive effect on the continuous improvement of higher education quality.…”
Section: Methods Research Hypothesesmentioning
confidence: 99%
“…A sociedade espera que a qualidade da educação esteja salvaguardada pelas instituições de ensino e pelos professores garantindo-se que as gerações futuras possam estar convenientemente preparadas para o mercado de trabalho (Hill, 1995).Nesse sentido é unânime que a qualidade do ensino nas universidades é fundamental para o sucesso da instituição e dos seus alunos, pois para além do foco nas avaliações orientadas para resultados momentâneos é fundamental prestar atenção ao trabalho dos professores e seus processos de ensino, sendo fundamental avaliar e monitorizar a sua qualidade (Chen, Chen, & Chen, 2011).…”
Section: Introductionunclassified
“…There are also special IT applications developed and available, such as "Teaching capability maturity model" (T-CMM) (Chena, Chenb, and Chenc, 2014) supporting QM of a teacher's individual teaching process and thus helping to improve the quality of the teaching process.…”
Section: Voluntary Additional Quality Assurance In Tertiary Educationmentioning
confidence: 99%